Gas chromatography selectivity of new phosphonium‐based dicationic ionic liquid stationary phases. Issue 22 (16th October 2018) - Patil, Rahul A.; Talebi, Mohsen; Sidisky, Leonard M.; Berthod, Alain; Armstrong, Daniel W.
Abstract: Three phosphonium‐based dicationic ionic liquids were synthesized as bis(trifluoromethylsulfonyl) imide salts. The three dications had a nonyl spacer between two identical phosphonium‐substituted groups. The three phosphonium moieties were dipropyl(phenyl), diphenyl(propyl), and diphenyl(toluyl). The physicochemical properties of the dicationic ionic liquids were appropriate to prepare 30 m capillary columns that were tested in gas chromatography. A unique selectivity compared to different polysiloxane or polar cyanosiloxane commercial columns was observed for selected mixes of phthalates, polyaromatic hydrocarbons, polychlorobiphenyls, and dioxins. Only minor selectivity variations were observed with the three dicationic ionic liquids. The different number of aromatic rings on the positively charged phosphonium group did not influence the dicationic ionic liquid selectivity significantly.